Nitridation of Al2O3 and GaAs surfaces by control enhanced ECR plasma - Mutoh, H; OKeeffe, P; Den, S; Komuro, S; Morikawa, T; Park, YJ; Hara, K; Munekata, H; Kukimoto, H (ELSEVIER SCIENCE BV, 1997)
An advanced compact electron cyclotron resonance (ECR) plasma source for low pressure processing is described. Selective control of the ion energy distribution independent of the plasma density is possible. The average ion energy is variable between 9 and 16 eV for a plasma density of 1.0 X 10(10) cm(-3). Nitrogen plasma induced surface reaction processes on Al2O3 and GaAs substrates were investigated. Control of the ion energy allows for superior AlN buffer layer properties on Al2O3. Moreover, control is provided while maintaining a high rate of nitridation. Low temperature GaAs nitridation by ECR plasma irradiation as a mask material for in-situ selective area growth on GaAs is also demonstrated, Nitridation reconstructs the surface to an amorphous like GaAsxN1-x configuration and nitrogen has been detected up to depths of 30 nm. In-situ removal of the nitride surface layer by hydrogen plasma etching has also been achieved.
Keywords: GAN FILMS; EPITAXY; GROWTH; LAYER